DAMPAK DEBU PABRIK SEMEN TERHADAP VEGETASI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
In developing clean cement factory, installing electrostatic precipator in the smoke stack performed prevention of particle pollution. Dust particles discharged. to the atmosphere could be mitigated with a so called "green or clean" program. Both of the mitigation techniques have been conducted by PT Semen Nusantara in Cilacap, Central Java. Leaf of trees surrounding the factory were seen entrap dust particles. The dust entrapped covered the surface of the leaves. On Termina/ia catapa leaves were found dust cover of 0.4071 mglcm2 compared ~o Filicium decipiens leaves of 0.4042 mglcm2 on a distance of 0.1 km from the factory. A distance of 2 km from the factory the dust cover of Terminalia catapa dan Filicium decipiens leaves decreased into approximately 0.3797 mglcm2and 0.3670 mglcm2respectively. The absorption and adsorption of cement dust are useful for human health and harmless for leaves.